Optimasi Adsorpsi Ion Krom III (Cr3+) sebagai Adsorben dengan Sistem Kontinu Menggunakan Adsorben Tanah Napa (Napa Soil) - Rahmatul Hayani; Mawardi Mawardi (Lembaga Yasin AlSys, 2026)
Exposure to chromium(III) ions in liquid waste can have adverse impacts on human health and the environment, thereby necessitating treatment methods that are effective, economical, and environmentally friendly. Various natural materials have been investigated as heavy metal adsorbents; however, studies that specifically evaluate tanah napa from Pesisir Selatan Regency as an adsorbent for Cr³⁺ in a column (continuous) system remain limited. This study aimed to determine the material characteristics and the optimum conditions for Cr³⁺ ion adsorption using activated tanah napa. The research employed an adsorption method in a continuous system, in which the adsorbent with a particle size of 200 mesh (70 µm) was prepared through calcination at 750°C and activation using 1 M KOH. Material characterization was carried out using X-ray Fluorescence (XRF) and Fourier Transform Infrared (FTIR) spectroscopy, while Cr³⁺ ion concentrations were analyzed using an Atomic Absorption Spectrophotometer (AAS). The results showed that the activation process increased the SiO₂ content to 65.781% and enhanced the presence of silanol and siloxane groups that play a role in the adsorption mechanism. The optimum conditions for Cr³⁺ adsorption were achieved at pH 4 with a capacity of 1.0686 mg/g, an initial concentration of 200 mg/L with a capacity of 0.3343 mg/g, and a flow rate of 20 drops/min with a capacity of 1.8464 mg/g. The decrease in adsorption capacity at higher pH values was associated with the formation of chromium hydroxide precipitates, whereas the increase in flow rate reduced the contact time between adsorbate and active sites on the adsorbent. These findings indicate that activated tanah napa has promising potential to be developed as a low-cost alternative adsorbent for heavy metal waste treatment in continuous systems.